Evaluation method of optimal load capacity of distribution network. (December 2022) - Bai, Hao; Yao, Ruotian; Pan, Shuhui; Li, Wei; Wang, Kelong; Ling, Wanshui
Abstract: To address the problems that current evaluation method about operation efficiency of distribution system fails to fully consider contradictory relationship between utilization economy and operation economy, this paper proposes an optimal load capacity (OLC) evaluation method for distribution network. Firstly, the measurement method of operation economy of distribution equipment is proposed, and then operation efficiency of distribution system is established by comprehensively considering utilization economy, operation economy, supply voltage quality and supply reliability. The effectiveness of evaluation method is verified in a distribution system.